PENGEMBANGAN SISTEM PENDUKUNG KEPUTUSAN BERBASIS MOBILE DALAM PEMILIHAN KUALITAS TELUR PADA KURNIAJAYA FARM - Ricco Herdiyan Saputra; Winia Waziana; Dita Novita Sari; Panji Andhika Pratomo (IDEALIS : InDonEsiA journaL Information System, 2025)
The demand for high-quality chicken eggs continues to increase, requiring an accurate and efficient assessment system to ensure the quality of products sold by egg agents. Kurniajaya Farm faces challenges in selecting the quality of chicken eggs that vary, so a technology is needed that can assist in objective decision making. This study aims to develop an egg quality assessment model using the simple additive weighting (SAW) method integrated into the mobile application development life cycle to facilitate the selection of quality chicken eggs. The application of the SAW method is due to its ability to simplify the assessment process by calculating the weight of various predetermined criteria. The criteria set in this study include egg size, egg weight, shell cleanliness, and shell thickness. The purpose of the study is to create a system that can help Kurniajaya Farm determine egg quality quickly, accurately and consistently through an easily accessible mobile application. The research findings indicate that the system development has succeeded in categorizing egg quality with high accuracy. Users can easily determine which eggs meet the desired quality standards through the mobile application. The implementation of this system at Kurniajaya Farm has been shown to improve the quality of the products produced and customer satisfaction.